2021
DOI: 10.1097/inf.0000000000003391
|View full text |Cite
|
Sign up to set email alerts
|

Haemophilus influenzae Serotype a as a Cause of Meningitis in Children in Brazil

Abstract: Background: Since the introduction of Haemophilus influenzae type b vaccines, invasive disease due to Haemophilus influenzae serotype a (Hia) has been reported with increasing frequency. Methods: This study is based on hospital-based surveillance for Hia meningitis over a 5-year period. Results: Thirty-five patients with H. influenzae meningitis were hospitalized and 12 were serotype a. Hia was detected in blood and cerebrospinal fluid by culture or reverse transcription polymerase chain reaction. Patients' me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…Consistently, we found that infants had the highest abundance of pathogenic species and rates of meningitis secondary to H. influenzae , and S. pneumoniae was highest among children <5 years of age ( 49 51 ). Meanwhile, S. pneumoniae was the main causative pathogen identified in all three age categories, and H. influenzae was only identified in infants and preschool children, which was in accordance with a previous Chinese report from Yunnan ( 52 ) and other studies from Sweden ( 53 ), Brazil ( 54 ), and England and Wales ( 55 ) but differed from data collected in mainland China ( 56 ). Most children and adolescents with viral CNS infections can recover completely in ~7 to 10 days without specific treatments ( 9 ).…”
Section: Discussionsupporting
confidence: 86%
“…Consistently, we found that infants had the highest abundance of pathogenic species and rates of meningitis secondary to H. influenzae , and S. pneumoniae was highest among children <5 years of age ( 49 51 ). Meanwhile, S. pneumoniae was the main causative pathogen identified in all three age categories, and H. influenzae was only identified in infants and preschool children, which was in accordance with a previous Chinese report from Yunnan ( 52 ) and other studies from Sweden ( 53 ), Brazil ( 54 ), and England and Wales ( 55 ) but differed from data collected in mainland China ( 56 ). Most children and adolescents with viral CNS infections can recover completely in ~7 to 10 days without specific treatments ( 9 ).…”
Section: Discussionsupporting
confidence: 86%
“…There are growing numbers of sporadic case reports, case series, and retrospective studies with various clinical presentations of invasive Hia infection globally. [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] Most of these reports show the greatest burden of invasive Hia disease in children ≤ 5 years or adults > 65 years, 32 with short-and long-term adverse outcomes exclusively in young children ≤ 5 years of age. 23,31,33 We described two cases of invasive Hia infection in children > 5 years of age who presented within a 2-month period to our hospital.…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] Most of these reports show the greatest burden of invasive Hia disease in children ≤ 5 years or adults > 65 years, 32 with short-and long-term adverse outcomes exclusively in young children ≤ 5 years of age. 23,31,33 We described two cases of invasive Hia infection in children > 5 years of age who presented within a 2-month period to our hospital. There was no identifiable epidemiological link between these patients and both cases were unrelated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations